SPH-based method to simulate penetrating impact mechanics into ballistic gelatin: Toward an understanding of the perforation of human tissue. (May 2019) - Al Khalil, Monzer; Frissane, Hassan; Taddei, Lorenzo; Meng, Shuangshuang; Lebaal, Nadhir; Demoly, Frederic; Bir, Cynthia; Roth, Sébastien
Abstract: This study aims to investigate the penetration of a projectile into a human tissue surrogate using meshless-based numerical method (SPH method). The ballistic gelatin being considered in the literature as a biofidelic human tissue simulant, 10% Ballistic Gelatin (BG) is impacted by a steel rigid sphere, and penetration time history as well as velocity are investigated, and compared to existing results of the literature. In addition, due to the paucity of experimental results to validate the numerical model, validation data are extended to analytical comparisons, giving interesting results for the analysis of the perforation of biological tissues by a projectile. Discussion of the simulations are also conducted based on existing results on 20% ballistic gelatin, coupling both 10% and 20% BG for an investigation of a multi-layered target, in order to approach the multi-layered behavior of the human body.